The Effectiveness of Using Serious Games to Improve Physics Learning Outcomes in Light Concept - Rudi Haryadi; Heni Pujiastuti (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
The purpose of this study was to determine the results of the use of serious games in physics learning in light material at Serang 6 Public High School. The research design used was the Pre-Test Randomized Control Group Post-Test Design. The population of the study was all of the eleventh grade students’ of Serang SMA 6 which numbered six classes. The study sample consisted of one experimental class (XI MIPA 1) and one control class (XI MIPA 2). The results showed that the application of physics learning used a serious game on light material in class XI of Serang 6 High School which took place very well and had a positive effect on student learning outcomes. In addition, the students’ response to the application of physics learning using the serious game was very good. The N-gain result shows that the use of the serious game is 0.89.